Review—Technology Trends of Poly-Si TFTs from the Viewpoints of Crystallization and Device Performance. (1st January 2019) - Matsuo, N.; Heya, A.; Hamada, H.
Abstract : Thin-film transistors (TFTs) utilizing low-temperature polycrystalline-Si (LTPS) are critical for system-on-panel applications. The requirements for LTPS are a high quality, a large grain size and position control of the nucleation. Many promising crystallization methods have been developed to satisfy these requirements. Herein, two scientific discoveries related to the low-temperature crystallization and high-performance TFT structure using the tunnel effect are introduced. Hydrogens in an amorphous (a-Si) film greatly accelerate the crystal velocity and improved the crystallinity of the excimer-laser annealing (ELA) poly-Si film, thereby providing a high-quality, a large-grained film referred to as secondary-grain film, under the solid-phase condition. In addition, a soft X-ray crystallization (SXC) method was developed. It reduces the threshold temperature of crystallization for a-Si, SiX Ge1-X and Ge films by 100°C–140°C in comparison to that for films prepared by conventional thermal crystallization. The SXC method is expected to become the critical low-temperature crystallization method in the era of the flexible electronics. On the other hand, although high-performance TFTs that utilize large single-crystalline grains have been intensively researched, such research has not been successful from the viewpoint of mass production. A novel device structure – tunneling dielectric TFT (TDTFT)–has been developed. The TDTFT reduces the gate-off current to less than 1/10 of that with a conventional TFT. In addition, the TDTFT improved the hump effect. We conclude that the triple-gate (Fin) TDTFT will be a promising candidate for next-generation poly-Si TFT structures.